Some methods of greenhouse gas utilization in hydrate form - Chiglintsev Igor; Nasyrov Azat (E3S Web of Conferences)
The article discusses methods for the artificial production of gas hydrates for the utilization of greenhouse gases. Experimental and theoretical works on the formation of hydrates are analyzed. The conditions for the formation of methane and carbon dioxide hydrates are presented, and the possibility of storing greenhouse gases in the form of hydrates in comparison with the compressed state is shown. Methods for producing hydrates by bubbling gases through water, intense mixing and exposure to pressure waves are considered. Methods for recycling greenhouse gases by injecting them into permafrost, underground formations and snow masses are described. Attention is paid to the duration of the hydrate formation process and methods of its intensification. The conditions for the effective production of hydrates for the utilization of greenhouse gases are considered. Technological schemes for the production of hydrates for their industrial use in order to reduce local greenhouse gas emissions are presented.